Considerações sobre invisibilidade social no Brasil e a identidade em busca de emancipação - Marques, Wilson de Azevedo (2010)
The objective of the research that gave origin to this text was to try to locate in our society, by means of it analyzes of innumerable readings and for being Brazilian, the question of the Social Invisibility that exists. The present study analysis brings the one of the History of the dictatorship period and after, and the society - subject object placing itself systematically in favorable situation in the first order of the benefits that has right and priority in the social evolution. Many explanations has been offered so that this vulnerability and invisibility are not remained or if they justify, enclosing since the attribution of guilt of the proper Brazilian nature until factors and weak questions and disinterested politics in the proposals of a social visibility. Much little the National State has contributed to stimulate the development of what really it interests, that is, to provide well-being of sectors of the population - what it would transform it, in effect to be able of State. We must consider that it has much to argue in responsibility terms administrative-politics, but we will examine only one brief period that in them seems to be a repetition of many others that had only appeared and imported in searching proper and to fortify them in the authoritarian model. This discussion involves the concept of invisibility which is followed by the conclusions of the true Republic with direct consequence in the society, preventing a dissociation of interests of State and Society. Still in the present study, we decline the theoretical inspiration of thinkers as Jurgen Habermas and its recent theoretical concerns. We do not forget , to appeal to other authors as Michael Foucault in its concern with the constitution of the citizen and Hannah Arendt giving emphasis in the social promotion as essential condition for the growth of a nation. Finally, the work suggests the recognition of the social identity as became a strong politics of the civil society and only factor essential to structuralize the State in its collaborating paper of the society